Current Issues in the Development of Diplomatic Activity at the International Level (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This scientific article examines some issues of the development of diplomatic activity, using the example of some problems emerging in modern international relations between states, trends in the development of the practice of coordinating their interests and attempts to find compromises in solving international problems. The relevance of the study lies in the fact that in the modern world the line between external and internal directions (priorities) of policies pursued by states is becoming unclear. Problems that were previously considered the internal affairs of a particular state can be solved at the international level. As part of the activities of state bodies for external relations, the range of departments that directly enter the international arena is constantly expanding. The purpose of the research in the scientific article is to study the key issues posed in the development of diplomatic activity at the international level. The research methodology covers the use of such methods of scientific knowledge as analysis, synthesis, induction, deduction, generalization, modeling and forecasting the development of diplomatic activity and service in the future. The results of the study will allow us to present current trends in the development of diplomatic activity at the international level in a systematic and logical form. Modern diplomatic activity includes a wide range of methods and tools for solving international problems. The challenges facing modern diplomats include international conflicts, terrorism, the proliferation of weapons of mass destruction, climate change, migration, trade and economic issues. To effectively solve these problems, diplomats often work in international organizations such as the United Nations, the European Union and others. Thus, modern diplomacy plays an important role in resolving international problems, based on dialogue, cooperation and respect for international law.